Behavior of transgender sex workers toward HIV/AIDS prevention in Makassar: A qualitative study - Serli; Eka Mayasari; Dian Meiliani Yulis (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: HIV/AIDS remains a critical public health issue in Makassar, with increasing cases reported across key populations, including transgender commercial sex workers (waria). Surveillance data indicate substantial HIV prevalence among waria, while behavioral factors such as limited knowledge, inconsistent preventive practices, and high-risk sexual networks contribute to ongoing transmission. This study explores the knowledge, attitudes, and preventive behaviors of transgender sex workers regarding HIV/AIDS. Methods: This qualitative study was conducted in 2011 along Jl. Perintis Kemerdekaan, Makassar. Data were collected through in-depth interviews, direct observation, and document review involving eight informants: seven transgender sex workers and one outreach worker from an NGO. Data were analyzed through reduction, narrative presentation, and thematic interpretation. Result: findings show that informants entered sex work due to early socialization, environmental influence, perceived enjoyment, and economic motives. Knowledge of HIV/AIDS varied; most informants recognized HIV as a virus that weakens the immune system, yet many were unable to differentiate clearly between causes and transmission routes. Attitudes toward peers living with HIV were generally positive, reflected by emotional support and encouragement to seek treatment. However, attitudes toward clients remained risky, with informants willing to engage in sexual activity even when clients showed symptoms of sexually transmitted infections. Preventive behaviors were inconsistent; although many preferred condom use, compliance depended heavily on client willingness. Self-treatment using non-prescribed medications was common, and formal healthcare utilization was limited. Conclusion: Transgender sex workers demonstrated partial understanding and inconsistent preventive practices related to HIV/AIDS. Strengthened health promotion, improved risk perception, and greater access to supportive services are essential to enhance safer behaviors and reduce HIV transmission within this population.